Contact investigations for outbreaks of Mycobacterium tuberculosis: advances through whole genome sequencing. - Walker, T; Monk, P; Smith, E; Peto, T (2013)
The control of tuberculosis depends on the identification and treatment of infectious patients and their contacts, who are currently identified through a combined approach of genotyping and epidemiological investigation. However, epidemiological data are often challenging to obtain, and genotyping data are difficult to interpret without them. Whole genome sequencing (WGS) technology is increasingly affordable, and offers the prospect of identifying plausible transmission events between patients without prior recourse to epidemiological data. We discuss the current approaches to tuberculosis control, and how WGS might advance public health efforts in the future.